SOCIALIZATION TO EMPOWER HOUSEWIVES ENTREPRENEURSHIP THE ARTS OF SEWING IN KUMBANG INDAH VILLAGE, BADAR DISTRICT, SOUTHEAST ACEH DISTRICT - Muhammad Yassir; Riyan Maulana; Habibul Akram; Ladipin; Muhammad Tahir (Jurnal Pengabdian Bangsa, 2023)
Implementation of Socialization to Empower Housewives to Be Entrepreneurs in the Art of Sewing in Kumbang Indah Village. The aim is for housewives to gain insight, knowledge about training programs, skills and entrepreneurial skills education. There is an increase in capacity and proficiency in skills, especially sewing, and an increase in the income of housewives who take part in the training program. In Kumbang Indah Village, Badar District, Southeast Aceh Regency.